2018
DOI: 10.18203/2349-3933.ijam20182944
|View full text |Cite
|
Sign up to set email alerts
|

Study of antiangiogenic activity of “aqueous extract of Nigella sativa seeds” in chick chorioallantoic membrane (CAM) model

Abstract: Background: Angiogenesis is important for the typical physiological activities such as cure from injury, menstrual cycle and embryo growth. It is also plays a crucial role in several pathological conditions in cancer. Antiangiogenesis, e.g., inhibition of blood vessel growth, is being investigated as a way to prevent the growth of tumors and other angiogenesis-dependent diseases. The chick embryo chorioallantoic membrane (CAM) is commonly used as an experimental in vivo assay to study both angiogenesis and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Oxygen supply and nutrients required for growth and survival of cancer was maintained through sprouting of new blood vessels from the established vasculature and creating a new vascular system within the tumor (38). Moreover, this neovascularization also plays significant role in tumor growth, invasion and metastasis (39). Cancer is considered to be angiogenic dependent disease and most of the studies successfully targeted various regulators of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen supply and nutrients required for growth and survival of cancer was maintained through sprouting of new blood vessels from the established vasculature and creating a new vascular system within the tumor (38). Moreover, this neovascularization also plays significant role in tumor growth, invasion and metastasis (39). Cancer is considered to be angiogenic dependent disease and most of the studies successfully targeted various regulators of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Tertiary blood vessels were also found to be decreased in the CAM area. Using the chick CAM model, Kota et al (2018) reported new pharmacological effects of Nigella sativa by the proven inhibition of angiogenesis30. Eva et al (2014) had found that ethanolic leaf extract of Antidesmabunis has anti-angiogenic activity when tested on duck embryos using CAM assay 31 .…”
Section: Fig 4: Histograms Showing the Patterns Of Cells Stained Withmentioning
confidence: 99%